5x-2[5(x+2)-(x-5)]-6

Question

Asked 11/16/2014 11:11:06 PM

Updated 11/17/2014 12:17:26 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [11/17/2014 12:17:26 AM]

s

-x + 5 = 2;

5 - 2 = x;

x = 3

Question

Asked 11/16/2014 11:11:06 PM

Updated 11/17/2014 12:17:26 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [11/17/2014 12:17:26 AM]

Rating

8

5x-2[5(x+2)-(x-5)]-6

Distribute

= 5x+ ( -2)(5(x+2))+( -2)( -x) + ( -2)(5) + -6

= 5x+ - 10x + -20 + 2x + -10 + -6

Combine like terms

= (5x+ -10x + 2x) + ( -20 + - 10 + -6)

= - 3x - 36

Distribute

= 5x+ ( -2)(5(x+2))+( -2)( -x) + ( -2)(5) + -6

= 5x+ - 10x + -20 + 2x + -10 + -6

Combine like terms

= (5x+ -10x + 2x) + ( -20 + - 10 + -6)

= - 3x - 36

Added 11/17/2014 12:17:25 AM

This answer has been confirmed as correct and helpful.

Simplify the expression 6m + 9m + 5. Then evaluate the expression for m = (-1)

Question

Updated 11/17/2014 12:13:31 AM

1 Answer/Comment

6m + 9m + 5. Then evaluate the expression for m = (-1)

(6)( -1) + (9)( -1) + 5

= -6 + (9) ( -1) + 5

= -6+ - 9 + 5

= - 15 + 5

= - 10

(6)( -1) + (9)( -1) + 5

= -6 + (9) ( -1) + 5

= -6+ - 9 + 5

= - 15 + 5

= - 10

Added 11/17/2014 12:13:31 AM

This answer has been confirmed as correct and helpful.

–(6x2 – 5x + 5)

Question

Updated 11/17/2014 12:10:43 AM

1 Answer/Comment

- (6x2 - 5x + 5) = - 6x2 + 5x - 5

Added 11/17/2014 12:10:42 AM

This answer has been confirmed as correct and helpful.

34,567,682

questions answered

There are no comments.